PENANGANAN KRISIS PADA PENERAPAN PERMENAKER NOMOR 2 TAHUN 2022 TENTANG PEMBAYARAN JAMINAN HARI TUA - Graha Wira Krida; Tina Maihasti (UNIVERSITAS PAKUAN, 2022)
A crisis is an unexpected, dramatic, sometimes unprecedented event that pushes an organization into chaos, and can destroy the organization without any real action. The policy of the Minister of Manpower Regulation (Permenaker) number 2 of 2022 regarding the payment of Old Age Protection (Jaminan Hari Tua / JHT)) provoked protests and strong criticism from workers. The payment of the old-age protections, which must wait until the age of the worker reaches 56 years, has an impact on the emergence of a wave of protests throughout Indonesia in the period from February to April 2022. In this study, researchers conducted a study on how the Ministry of Manpower's public relations team (Kemenaker RI) who were members of the Ministry of Manpower crisis team tried to get through this crisis well. This study uses a qualitative descriptive method by taking research data with interviews, documentation, and literature studies. Researchers want to find out more about the causes of the crises that occurred, what are the stages of the crises that they went through and what real conditions emerged that could be observed, and strategies for managing the crises that occurred. The results of the study can show that the cause of this crisis is a crisis of confrontation due to widespread protests and criticism from workers throughout Indonesia, then the stages of the crisis include the phases of prodromal crisis, acute crisis, chronic crisis, and resolution crisis.